Evaluation of body mass index and lipid fractions levels in patients with retinal artery occlusion - Risimić Dijana; Nikolić Dejan; Jakšić Vesna; Simeunović Dejan; Milenković Svetislav; Stefanović Ivan; Jaković Nataša; Milić Nada; Cekić Sonja; Babović Siniša (Vojnosanitetski Pregled)
Background/Aim. There are studies stressing out that atherosclerosis is most common associated systemic condition in patients with retinal artery occlusion. The aim of this study was to analyze values of body mass index and lipid fractions in healthy individuals and patients with retinal artery occlusion. Methods. This study included 90 participants during a 6-year period. The population was divided into 2 groups: the group with the diagnosed retinal artery occlusion and the group without retinal artery occlusion. The observed parameters were as follows: body mass index, low and high density lipoproteins and triglycerides. Results. The study revealed no significant difference regarding body mass index and triglycerides values between the two evaluated groups, while low and high density lipoproteins values were significantly higher in the group of patients with retinal artery occlusion. Conclusions. The study demonstrated that body mass index and triglycerides have less important role in atherogenic pathogenesis of retinal artery occlusion, while low density lipoprotein is the fraction that is shown to be most potent in such etiological processes.